Interleukin-6 Is a Biomarker for the Development of Fatal Severe Acute Respiratory Syndrome Coronavirus 2 Pneumonia - Santa Cruz, André; Mendes-Frias, Ana; Oliveira, Ana Isabel; Dias, Luís; Matos, Ana Rita; Carvalho, Alexandre; Capela, Carlos; Pedrosa, Jorge; Castro, António Gil; Silvestre, Ricardo (Frontiers in Immunology, 2021)
Hyper-inflammatory responses induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are a major cause of disease severity and death. Predictive prognosis biomarkers to guide therapeutics are critically lacking. Several studies have indicated a “cytokine storm” with release of IL-1, IL-6, IL-8, along with tumor necrosis factor alpha (TNFα) and other inflammatory mediators. Here, we proposed to assess the relationship between IL-6 and Coronavirus Disease 2019 (COVID-19) patient’s outcomes. Our cohort consisted of 46 adult patients with PCR-proven SARS-CoV-2 infection admitted in a COVID-19 ward of the Hospital de Braga from 7th April to 7th May 2020, whose IL-6 levels were followed over time. We found that IL-6 levels were significantly different between the disease stage. Also, we found a significant negative correlation between IL-6 levels during stage IIb and III and peripheral oxygen saturation (SpO2), partial pressure of oxygen in arterial blood (PaO2), showing that IL-6 correlates with respiratory failure. Comparing to the inflammatory markers available in the clinic routine, we found a positive correlation between IL-6 and CRP. However, when we assessed the predictive value of these two markers, IL-6 behave as a better predictor of disease progression. In a binary logistic regression, IL-6 level was the most significant predictor of the nonsurvivors group, when compared to age and CRP. Herein, we present IL-6 as a relevant tool for prognostic evaluation, mainly as a predictor of outcome.